Electroconvulsive therapy (ECT) from the patient's perspective - Hersh, K. (Journal of medical ethics, 2013)
This is a response to Dr Charlotte Rosalind Blease's paper ‘Electroconvulsive Therapy (ECT), the Placebo Effect and Informed Consent’, written by Julie K. Hersh who has had ECT. Hersh argues that placebo effect is impossible to prove without endangering the lives of participants in the study. In addition, informing potential ECT patients of unproven placebo effect could discourage patients from using a procedure that from experience has proven highly effective.